Edible film production with aloe vera extract and its printability - BİRTANE, HATİCE (My University, 2022)
The main concern with protecting fruits and vegetables from bacterial infection and growth is ensuring product quality and safety. Hydroxyethyl cellulose, with –OH in the natural cellulose molecule substituted by a hydroxyethyl group, has been widely used in oil exploitation, coating, medicine, food and polymerization process. It is nontoxic and low-cost. Aloe vera is a well-known herbal plant that is used for its therapeutic properties. The gel extracted from Aloe vera plants contains a variety of biologically active compounds, phenolic contents, and minerals. In this study, the edible films containing different proportions of aloe vera and hydroxyl ethyl cellulose were prepared. The structural and antibacterial properties of the obtained edible films were examined. The obtained films were printed with inkjet. Color and adhesion properties of printed samples were determined and it was observed that the edible films showed antibacterial properties.
Keywords: Bilgisayar Bilimleri; Bilgisayar Grafiği; Mühendislik ve Teknoloji; Computer Sciences; Computer Graphics; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; BİLGİSAYAR BİLİMİ, İNTERDİSİPLİNER UYGULAMALAR; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; COMPUTER SCIENCE, INTERDISCIPLINARY APPLICATIONS; Bilgisayar Grafikleri ve Bilgisayar Destekli Tasarım; Fizik Bilimleri; Bilgisayar Bilimi Uygulamaları; Computer Graphics and Computer-Aided Design; Physical Sciences; Computer Science Applications; aloe vera; Edible film; hydroxyethyl cellulose; printability; Edible film; hydroxyethyl cellulose; aloe vera; printability